Improving India's Saving Performance - Muhleisen, Martin (IMF Working Papers; Working Paper ;, 1997)
This paper discusses recent trends in Indian saving behavior and reviews policy options to increase domestic saving. In the absence of forceful policy measures, private saving would continue to rise gradually, but probably not by enough to finance the government's growth target of 7 percent over the next decade. The most promising way to boost domestic saving would be through increased public saving and a strong structural reform program, including financial liberalization, which would initiate a virtuous growth-saving circle. To increase the efficiency of the savings allocation, particular attention should be paid to long-term saving instruments.